Anxiety, Uncertainty, and Resilience During the Pandemic Period - Anthropological and Psychological Perspectives 2021
DOI: 10.5772/intechopen.98997
|View full text |Cite
|
Sign up to set email alerts
|

Pleasant Activities among Young Adults and Their Lack during the COVID-19 Pandemic

Abstract: The pandemic COVID-19 burst in the Slovak Republic in March of the 2020 year. Subsequently, the schools were closed on the 10th of March and the everyday life in the country was for a long uncertain time questionable. The curfew slowed down the outdoor activities and has brought sudden changes also in the lives of young active people. This can be a time of uncertainty, and the stress. To do some pleasant activities can act as a stress reliever, but in the pandemic time not all pleasant activities can be realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The findings [8] resulted in outcomes, which are statistically significant that sporting activity has a more positive impact on subjective dimensions of quality of life in adolescent sports-active boys and girls than in adolescent sports-inactive boys and girls. The decrease in physical activity during the last time in period of the COVID-19 pandemic brought evidence that the lack of sporting activities was mainly represented by activities related to outdoor sports (outdoor exercising, swimming in the pool, downhill skiing), exercising in a fitness centre or playing sports games, where the presence of other players is required (football in men and volleyball in women) [10]. In the review [48], happiness is regarded as a correlate of genetic determinants (genes, personality), circumstantial and demographic factors (gender, age, intelligence, wealth, religion, societal condition, health) and individual control (social relationship, marriage and children, leisure, goals).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings [8] resulted in outcomes, which are statistically significant that sporting activity has a more positive impact on subjective dimensions of quality of life in adolescent sports-active boys and girls than in adolescent sports-inactive boys and girls. The decrease in physical activity during the last time in period of the COVID-19 pandemic brought evidence that the lack of sporting activities was mainly represented by activities related to outdoor sports (outdoor exercising, swimming in the pool, downhill skiing), exercising in a fitness centre or playing sports games, where the presence of other players is required (football in men and volleyball in women) [10]. In the review [48], happiness is regarded as a correlate of genetic determinants (genes, personality), circumstantial and demographic factors (gender, age, intelligence, wealth, religion, societal condition, health) and individual control (social relationship, marriage and children, leisure, goals).…”
Section: Discussionmentioning
confidence: 99%
“…Authors [3] present that in adolescent, neurodevelopment occurs in brain regions associated with motivation, impulsivity and addiction. The adolescent years are characteristic of changes in body composition, physical fitness and behavioural changes in participation in physical activity, especially in adolescent girls [4][5][6][7][8][9][10][11]. Comparison of some opinions on perceiving one's body in the research by [6] shows that the research results revealed that the most satisfied with their body image were sports-active adolescent boys, and the highest pride in their own bodies in terms of attractiveness felt sports-active adolescent boys as well.…”
Section: Adolescencementioning
confidence: 99%
See 1 more Smart Citation